A ribosomal marker-based metataxonomic framework for environmental surveillance of nematodes of public health importance - Juan P. Zuluaga; Katherine Bedoya-Urrego; Juan F. Alzate (PLOS One, 2026)
Metataxonomic analysis targeting the V4 region of the 18S rDNA gene, combined with molecular phylogenetic inference, was applied to detect nematode DNA of public health relevance in environmental matrices. A total of 25 mOTUs corresponding to six nematode taxa were detected in environmental samples from the Andean region of Colombia. Analysis of 12 water and sludge samples from wastewater treatment plants, 5 artisanal agricultural bioinputs, and 3 food samples revealed multiple species of public health significance: Trichuris trichiura , Enterobius vermicularis , Ascaris spp., and Necator americanus. We also confirmed zoonotic species, including Angiostrongylus cantonensis and Trichinella spp . These findings demonstrate that combining metataxonomics with molecular phylogeny provides a scalable molecular framework for the environmental surveillance of parasitic nematodes, overcoming the limitations of traditional morphological identification methods. This approach offers a replicable model for strengthening control and monitoring programs for parasitism in human populations.